Studi Pemisahan Aliran Dasar Metode Local Minimum Method Daerah Aliran Sungai Miu - Oktavia, S.R.; Mantika, O.A.; Rugaiyah, Rugaiyah (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2021)
The two main elements of a river flow hydrograph are direct runoff and baseflow. Base flow is a flow that comes from groundwater and it is available during the rainy and dry seasons. Information of baseflow value of a watershed has an important meaning in efforts to develop and manage water resources, including the provision of clean water, irrigation systems, flood management and others. Miu watershed located in Sigi Regency often experiences natural disasters such as floods and droughts that occur almost every year, which is the research location with an area of 65,452.01 Ha. This study aims to determine the value of baseflow using the Local Minimum Method and to find out whether this method can be used for baseflow modeling in research watersheds. This study was conducted using Hydro Office software with input data in the form of daily discharge data from 2004 to 2013. The average baseflow value obtained was 5.43 m3/s. The process of calibrating the baseflow value by taking flow data in the dry season where there is no rainfall input. It is obtained that BFI have value an average of 0.89. This value indicates that the Miu watershed has high storage permeability characteristics, The Miu watershed has quite stable flow during dry periods, because the greater the BFI value, the better the water supply in a watershed. In the statistical test, the observed discharge is the discharge data from the measurement results for the period 2004-2013, while the calculated discharge is the result of the estimated base flow value obtained using the graphical method. From the results of the statistical test of RMSE and R2, the RMSE value was 0.147 and the R2 value was 0.751. Both statistical tests show that the local minimum method has a fairly good performance in modeling the base flow in the Miu watershed.